E-wallet: Make generation z more consumptive? - Ichwan, Afiful (Indonesian Journal of Islamic Economics Research, 2025)
The development of e-wallets has made life simpler, changed the way people think and act, but it has also fostered consumerism and repetitive transactions. The author's goal is to examine how the transaction patterns of Generation Z changed before and after they started using e-wallet applications, since Generation Z is the primary user of e-wallet apps. The study used non-probability sampling and targeted sampling to include 240 members of Generation Z from the city of Lampung, the provincial capital. To determine whether there were any significant differences, the Paired Sample T-Test was the analytical technique used. The paired sample T-test yielded a statistically significant p-value of 0.000, which is less than 0.05. This indicates a variation in e-wallet transaction patterns before and after acquiring an e-wallet. While e-wallet transaction patterns are increasing, not all transactions are consumptive-oriented, but e-wallets have the potential to make consumers more productive.